Kajian Toksisitas Serbuk Biji Mahoni terhadap Perkembangan Tingkah Laku, Histologi Hati serta Hematologi Anak Mencit - Hilmarni Hilmarni; Almahdy Almahdy; Helmi Arifin (Jurnal Sains Farmasi & Klinis, 2015)
This study aims to determine the effect of seed powder mahogany (Swietenia macrophylla King) on the development of behavior, liver histology and hematology of pups mice. Experimental animals used were 45 female mice were divided randomly into 5 groups. Group 1 as a control group. Groups 2, 3, 4, and 5, respectively mahogany seed powder given at a dose of 5, 10, 15, and 20 mg/20g/day from fetal life until lactation is completed. Developmental toxicity test carried out by behavioral test battery, observation of histology and hematology profile. The results showed that the provision of mahogany seed powder causes abnormal in the conduct reflex test and motor test on post natal day of 8 and 10, as well as the vision test on post natal day of 14-18. While the observation of liver histology and hematology profile did not show any effect.